2019
DOI: 10.1021/acs.energyfuels.9b02284
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Multiscale Approach to Study the Initial Steps Involved in the Chemical Reactivity of Soot Precursors

Abstract: In the present study bond formation reactions between soot precursors and their role in the soot inception process is investigated. The soot precursors were generated in macroscopic detailed gas-phase kinetic calculations and according to certain criteria introduced in simulation boxes to model bond formation between soot precursor molecules with reactive force field molecular dynamics modeling. The impacts of temperature, fuel mixture and equivalence ratio have been investigated on the rate and structure of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 99 publications
2
5
0
Order By: Relevance
“…The molecular formulae are consistent with benzenoid PAHs (C 14 H 10 + , C 16 H 10 + , and C 18 H 12 + ), PAHs containing 5-member rings (C 12 H 8 + and C 16 H 10 + ), radical ions obtained from hydrogen elimination reactions from PAHs containing a fivemember ring (C 13 H 9 + , C 15 H 9 + , and C 17 H 11 + ), and sidesubstituted PAHs (C 16 H 12 + ). These molecular formulae are also consistent with the structural formulae proposed in soot formation models based on the dimerization of low-mass PAHs 13,[15][16][17][18][19] . The many correspondences between sums of pairs of m/z in mode 1 with individual m/z in mode 2 suggest that the dimerization of C12-C20 hydrocarbons having individual [H] 0.35-0.43 followed by the formation of C-C covalent bonds occurs in the flame axis immediately upstream soot formation.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The molecular formulae are consistent with benzenoid PAHs (C 14 H 10 + , C 16 H 10 + , and C 18 H 12 + ), PAHs containing 5-member rings (C 12 H 8 + and C 16 H 10 + ), radical ions obtained from hydrogen elimination reactions from PAHs containing a fivemember ring (C 13 H 9 + , C 15 H 9 + , and C 17 H 11 + ), and sidesubstituted PAHs (C 16 H 12 + ). These molecular formulae are also consistent with the structural formulae proposed in soot formation models based on the dimerization of low-mass PAHs 13,[15][16][17][18][19] . The many correspondences between sums of pairs of m/z in mode 1 with individual m/z in mode 2 suggest that the dimerization of C12-C20 hydrocarbons having individual [H] 0.35-0.43 followed by the formation of C-C covalent bonds occurs in the flame axis immediately upstream soot formation.…”
Section: Resultssupporting
confidence: 87%
“…Although the thermodynamic data of many PAHs are still subject to uncertainty, the reversibility of a nucleation process hypothetically driven by the dimerization of small PAHs has been used to successfully reproduce soot volume fraction profiles 9,10 and NSP size distributions 11 in several laboratory flames. To explain the dimerization of PAHs at high temperature, the formation of covalent carbon-carbon bonds between PAH monomers [12][13][14][15][16][17][18] , or alternatively rapid radical-driven clustering reactions 19,20 , has been invoked. The hydrogen abstraction acetylene addition (HACA) mechanism, the defining feature of which is the kinetic-thermodynamic coupling, has also been recently generalized by postulating the formation of doubly bonded covalent bridges between PAHs 18 .…”
mentioning
confidence: 99%
“…[30][31][32] They added a chemical bond formation term that describes the formation of chemical bonds between PAHs and thus the scientific discussion currently shifts towards aliphatically bridged PAHs. 28,[33][34] These hypothesized compounds have only recently been identified in flame-sampling tandem mass spectrometry experiments. 35 In the same work, aliphatically substituted PAHs were identified, which might be of significance for particle inception as Violi and coworkers have shown that their dimers are more likely to survive elevated flame temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…5(d). The unstable AALH structures further evolve into a peri-condensed plane through rearrangement and ring closure, 9 leading to aromatic peri-condensed polycyclic hydrocarbon (APPH) structures at 1.5 ns. An aromatic directly linked hydrocarbon (ADLH) is also observed at around 1.6 ns.…”
Section: Incipient Soot Formation Mechanism Of Diesel Combustionmentioning
confidence: 99%
“…The concentration of these PAH species in the gas phase during combustion is low, which is contradictory to the phenomenon that nascent soot was observed before the concentration peaks of these PAH species. 9 The hypothesis of the dimerization of PAHs with a larger size in the soot nucleation process therefore appears highly unlikely. It is speculated that some stronger interactions are prerequisite for soot nucleation, such as covalent bonds combining PAH radicals and aryl radicals, but the existing theories are still inadequate to explain the rapidly persistent mass growth and the gas-to-solid nucleation process in the post flame region.…”
Section: Introductionmentioning
confidence: 99%